2005
DOI: 10.1016/s0002-9440(10)62497-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ8-Mediated Activation of Transforming Growth Factor-β by Perivascular Astrocytes

Abstract: Brain hemorrhage is a severe complication of both neoplastic and nonneoplastic brain disease. Mice deficient in the alpha(v)beta8 integrin display defective brain vessel formation resulting in hemorrhage and perinatal death, but the mechanism of brain hemorrhage is unknown. Because the alpha(v)beta8 integrin is expressed by astrocytes and not expressed by endothelium, paracrine interactions between astrocytes and endothelial cells could contribute to the maintenance of brain vessel integrity. We have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 43 publications
8
151
1
Order By: Relevance
“…The discrepancy between these 2 studies likely represents inherent cell type-specific differences between airway and dermal fibroblasts. For instance, we have found that unlike human airway fibroblasts, human dermal fibroblasts do not express α v β 8 (53). However, it is likely that there are other differences between airway epithelial cells and keratinocytes in the cofactors that they secrete that can modify fibroblast responses to IL-1β.…”
Section: Figurementioning
confidence: 88%
“…The discrepancy between these 2 studies likely represents inherent cell type-specific differences between airway and dermal fibroblasts. For instance, we have found that unlike human airway fibroblasts, human dermal fibroblasts do not express α v β 8 (53). However, it is likely that there are other differences between airway epithelial cells and keratinocytes in the cofactors that they secrete that can modify fibroblast responses to IL-1β.…”
Section: Figurementioning
confidence: 88%
“…Glial endfeet are closely juxtaposed to most blood vessels in the CNS. Indeed, while this manuscript was under review, immunoelectron microscopy localized ␣v␤8 to perivascular glial endfeet (21). In the adult brain, Band 4.1N, but not Band 4.1B, was also expressed in a perivascular pattern (Fig.…”
Section: Band 41b Selectively Interacts With ␤8mentioning
confidence: 90%
“…The integrin ␣v␤8 is of particular interest because it is the only ␣v subunit-containing integrin that has been shown to be essential for development (8 -14). The integrin ␤8 subunit is expressed in various epithelial (squamous mucosa, airway epithelium, renal tubular epithelium, and neuroepithelium) (1,(15)(16)(17), mesenchymal (fibroblasts, kidney mesengial cells, and astrocytes) (18,19), and select immune cell types (splenocytes, CD44…”
mentioning
confidence: 99%